Diagnostik Kesulitan Belajar Siswa Pada Materi Trigonometri Kelas XI Multimedia SMKN 2 Sinjai - David Adrian Fachrezi Derek; Zazirah Maqfirah; Nurbaitul Afyan; Nurjannah Nurjannah (IAI Muhammadiyah Sinjai, 2022)
This research was conducted at SMKN 2 Sinjai. This study aims to describe students' learning difficulties in mathematics on trigonometric material. The method applied in this research is descriptive qualitative research method. The subjects in this study were two students of class XI Multimedia at SMKN 2 Sinjai. The research techniques used in this study were observation, diagnostic tests and interviews. The results of this study indicate that the difficulties experienced by FD and SC subjects are difficulties in using the Pythagorean formula in determining one side length of a right triangle and applying the trigonometric comparison formula in solving real problems. Efforts that can be made in overcoming the difficulties experienced by students are teachers need to pay attention to the characteristics of their students and increase their interest in learning mathematics.